Investigation of the impact of clonal hematopoiesis on severity and pathophysiology of COVID-19 in rhesus macaques - Shin, Tae-Hoon; Zhou, Yifan; Lee, Byung-Chul; Hong, So Gun; Andrew, Shayne F.; Flynn, Barbara J.; Gagne, Matthew; Todd, John-Paul M.; Moore, Ian N.; Cook, Anthony; Lewis, Mark G.; Foulds, Kathryn E.; et al. (Frontiers in Veterinary Science, 2023)
Clinical manifestations of COVID-19 vary widely, ranging from asymptomatic to severe respiratory failure with profound inflammation. Although risk factors for severe illness have been identified, definitive determinants remain elusive. Clonal hematopoiesis (CH), the expansion of hematopoietic stem and progenitor cells bearing acquired somatic mutations, is associated with advanced age and hyperinflammation. Given the similar age range and hyperinflammatory phenotype between frequent CH and severe COVID-19, CH could impact the risk of severe COVID-19. Human cohort studies have attempted to prove this relationship, but conclusions are conflicting. Rhesus macaques (RMs) are being utilized to test vaccines and therapeutics for COVID-19. However, RMs, even other species, have not yet been reported to develop late inflammatory COVID-19 disease. Here, RMs with either spontaneous DNMT3A or engineered TET2 CH along with similarly transplanted and conditioned controls were infected with SARS-CoV-2 and monitored until 12 days post-inoculation (dpi). Although no significant differences in clinical symptoms and blood counts were noted, an aged animal with natural DNMT3A CH died on 10 dpi. CH macaques showed evidence of sustained local inflammatory responses compared to controls. Interestingly, viral loads in respiratory tracts were higher at every timepoint in the CH group. Lung sections from euthanasia showed evidence of mild inflammation in all animals, while viral antigen was more frequently detected in the lung tissues of CH macaques even at the time of autopsy. Despite the lack of striking inflammation and serious illness, our findings suggest potential pathophysiological differences in RMs with or without CH upon SARS-CoV-2 infection.